2021
DOI: 10.1007/s11135-021-01156-0
|View full text |Cite
|
Sign up to set email alerts
|

The qualitative pretest interview for questionnaire development: outline of programme and practice

Abstract: Good survey research depends on asking the right questions; it is the only way to ensure that the information collected from respondents is suitable for providing good answers to our research questions. The article discusses and advocates a comprehensive consideration of qualitative-interpretive methodology in open forms of pretesting for the evaluation of draft survey questionnaires. We outline an approach we call Qualitative Pretest Interview (QPI). It transfers the idea of negotiated common understanding in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Interestingly, students pointed to various benefits stemming from volunteering, which included the normative ones (being useful for the community, participating in something important, fulfilling the civic duty, public service, and helping others), personal enhancement (psychological development and personal growth, realization of one’s passion, or having a sense of pride), career (learning new knowledge and skills, building and developing personal career, gaining professional experience, making useful contacts, interprofessional collaboration, or obtaining the academic credit) and social (new relationships with others, making new friends, working with other people, and respect from others). However, most respondents suggested that the pandemic was a unique teaching moment and active involvement in volunteering created new learning opportunities, especially in the field of competency-based medical education and project problem-based learning [ 11 , 39 , 49 , 50 , 51 , 52 ]. Indeed, in addition to altruistic and value-driven motivations, most participants recognized that the pandemic gave them a chance to gain new knowledge and improve their social, organisational, and stress management skills, and helped them to understand how the health system works as a multidisciplinary whole [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, students pointed to various benefits stemming from volunteering, which included the normative ones (being useful for the community, participating in something important, fulfilling the civic duty, public service, and helping others), personal enhancement (psychological development and personal growth, realization of one’s passion, or having a sense of pride), career (learning new knowledge and skills, building and developing personal career, gaining professional experience, making useful contacts, interprofessional collaboration, or obtaining the academic credit) and social (new relationships with others, making new friends, working with other people, and respect from others). However, most respondents suggested that the pandemic was a unique teaching moment and active involvement in volunteering created new learning opportunities, especially in the field of competency-based medical education and project problem-based learning [ 11 , 39 , 49 , 50 , 51 , 52 ]. Indeed, in addition to altruistic and value-driven motivations, most participants recognized that the pandemic gave them a chance to gain new knowledge and improve their social, organisational, and stress management skills, and helped them to understand how the health system works as a multidisciplinary whole [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the study focussed on the students’ lived experiences, the meanings they gave to those experiences and the choices they made based on those meanings, an interpretative phenomenological approach was used for this study [ 38 ]. The questionnaire was developed according to the Qualitative Pretest Interview (QPI) approach [ 39 ]. Thus, the initial list of the interview questions was developed after a thorough analysis of academic literature on the medial students’ volunteering during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…This is a chance for the questionnaire designer to learn whether there is any uncertainty about any of the items as well as whether participants have any recommendations on how the items can be improved ( Tsang et al., 2017 ). Consequently, the author assessed the questionnaire, in the pilot test, based on a number of factors, including its relevance, conciseness, and practicality, as well as language and item sequencing ( Buschle et al., 2021 ). Fortunately, there were no concerns about the clarity of the items or the questionnaire's acceptability.…”
Section: Methodsmentioning
confidence: 99%
“…Making of the questionnaire can be developed from the topic related questions that make the consideration about the chosen topic and the participants should be authentic to respond to the question. As mentioned by Buschle et al (2022), the questionnaire development is much vital for the research work that makes the better responses to have the collection of ethical primary data.…”
Section: Sampling Methodsmentioning
confidence: 99%